Blood Passion: The Ludlow Massacre and Class War In the American West - Norwood, Stephen H. (Labour / Le Travail, 2009)
The article reviews the book, "Blood Passion: The Ludlow Massacre and Class War in the American West," by Scott Martelle.
Keywords: BLOOD Passion: The Ludlow Massacre & Class War in the American West (Book); BOOKS – Reviews; MARTELLE; Scott; Nonfiction; violence